United States : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United States. (IMF Staff Country Reports; Country Report, 2022)
The U.S. economy has staged a strong recovery from the COVID-19 shock. The positive effects of unprecedented policy stimulus, combined with the advantages of a highly flexible economy, have been clear. Just over two years after the COVID-19 shock, the unemployment rate and other measures of labor force underutilization have returned to end-2019 levels and output is close to its pre-pandemic trend. Rapid wage increases for lower income workers have reduced income polarization and poverty fell in 2020. On net, 8.5 million jobs have been created since the end of 2020. In addition, the swift policy response was able to maintain the smooth functioning of U.S. financial markets and prevent the surge of bankruptcies that many had feared.